Two eriophyoid mites (Acari: Eriophyoidea) associated with Ilex paraguariensis from Brazil - Da Silva, Guilherme Liberato; Esswein, Isadora Zanatta; Dameda, Catiane; Ferla, Noeli Juarez (Zootaxa, 2017)
Diptilostatus chimarricus n. sp. is described based on specimens collected on Ilex paraguariensis A. St.–Hill. (Aquifoliaceae), commonly known as yerba mate, from southern Brazil. It is the third eriophyoid mite species reported on I. paraguariensis in Brazil. This new species caused no observable damage to its host plant. A key to species of Diptilostatus is provided. Dichopelmus notus Keifer, 1959, also from yerba mate, is redescribed.